A reliable transmission scheme for 3D point cloud based on partial decode-and-forward relay over burst error fading channel. (18th February 2022) - Hao, Jianjun; Liu, Luyao; Chen, Wei
A reliable and efficient transmitting scheme based on partial decode-and-forward (PDF) relaying for UAV-ground wireless communication system is proposed in this article. In a multi-UAVs to ground case, we implement a 3D point cloud transmission system based on: 1) Polar-RS concatenated channel coding; 2) a relay adopt partial decode-and-forward strategy. Hence, simulations for point cloud transmitting over a burst jamming channel and a burst deep fading channel are performed respectively. The simulation results show that Polar-RS code achieves higher reliability against burst error channel than RS-Polar scheme does under the same codeword length and code rate, also the proposed PDF relay reduces the time delay and implementation complexity compared to the full decode-and-forward (FDF) scheme.